A designed, phase changing RTX-based peptide for efficient bioseparations. (April 2013) - Shur, Oren; Dooley, Kevin; Blenner, Mark; Baltimore, Matthew; Banta, Scott
Typically, chromatography is the most costly and time-consuming step in protein purification. As a result, alternative methods have been sought for bioseparations, including the use of stimulus-responsive tags that can reversibly precipitate out of solution in response to the appropriate stimulus. While effective, stimulus-responsive tags tend to require temperature changes or relatively harsh buffer conditions to induce precipitation. Here we describe a synthetic peptide, based on the natural repeat-in-toxin (RTX) domain that undergoes gentler calcium-responsive, reversible precipitation. When coupled to the maltose binding protein (MBP), our calcium-responsive tag efficiently purified the fusion protein. Furthermore, when the MBP was appended to green fluorescent protein (GFP), β-lactamase, or a thermostable alcohol dehydrogenase (AdhD), these constructs could also be purified by calcium-induced precipitation. Finally, protease cleavage of the precipitating tag enables the recovery of pure and active target protein by cycling precipitation before and after cleavage.